Pain Management Strategies for Urogynecologic Surgery. Issue 3 (March 2015) - Collins, Sarah A.; Joshi, Girish; Quiroz, Lieschen H.; Steinberg, Adam C.; Nihira, Mikio A.
<x xml:space="preserve">Abstract</x> ABSTRACT Surgery-related pain is common and is difficult to manage during the postoperative period. In some studies, more than 30% of patients who underwent either vaginal surgery or abdominal surgery reported inadequate pain control at postoperative days 3 and 7. Poor pain control during the acute postoperative period causes heightened sympathetic discharge (increasing the risk for myocardial infarction and stroke) and decreased ambulation (increasing the risk for thromboembolism). Poor acute postoperative pain control can also result in poor inspiratory effort, resulting in an increased risk for postoperative pneumonia, and central sensitization with resultant chronic pain sequelae. Opioid drug therapy is the current mainstay for management of acute postoperative pain. However, opioid-related adverse drug events occur frequently after gynecologic surgery. Problems such as nausea, vomiting, constipation, drowsiness, sedation, and respiratory depression are common with opioids and often require additional treatment, prolonging the postoperative length of stay. Innovative pain management regimens that minimize opioid use are necessary. The aims of this review were to examine recent evidence on surgical pain management strategies and to identify pain control methods used in urogynecologic surgery. The authors hoped to use existing evidence to suggest future pain management strategies in urogynecologic surgery. A search of PubMed and MEDLINE databases was performed to identify articles on pain control methods in gynecologic surgery published between 2007 and December 2012. Articles with evidence-based recommendations were identified, which included the following: pain management strategies (preemptive, multimodal), route of surgery, and timing of anesthetic intervention (preoperative, intraoperative, and postoperative). The initial search identified 126 articles meeting inclusion and exclusion criteria. Few randomized trials describing specific pain management strategies in urogynecologic surgery were identified. Therefore, quality randomized trials on pain management methods used in other gynecologic procedures were included if their findings appeared to be applicable to urogynecologic procedures. Evidence from such studies suggested that a number of preemptive and multimodal analgesia strategies used for abdominal, laparoscopic, and vaginal gynecologic surgery reduced pain and opioid-related adverse events. Multimodal analgesia involves the use of several interventions with different mechanisms of action. Preemptive analgesia involves initiation of anesthetic efforts before surgery. Evidence from preoperative, intraoperative, and postoperative pain management strategies used in gynecologic surgery was presented. This review identified limited procedure-specific evidence to guide pain management for urogynecologic procedures. Future studies are needed on procedure-specific pain control strategies in urogynecologic surgery, especially those incorporating multimodal and preemptive approaches.